Characteristics of very high‐energy electron beams for the irradiation of deep‐seated targets. Issue 7 (16th May 2021) - Böhlen, Till Tobias; Germond, Jean‐François; Traneus, Erik; Bourhis, Jean; Vozenin, Marie‐Catherine; Bailat, Claude; Bochud, François; Moeckli, Raphaël
Abstract : Purpose: Driven by advances in accelerator technology and the potential of exploiting the FLASH effect for the treatment of deep‐seated targets (>5 cm), there is an active interest in the construction of devices to deliver very high‐energy electron (VHEE) beams for radiation therapy. The application of novel VHEE devices, however, requires an assessment of the tradeoffs between the different beam parameter choices including beam energies, beam divergences, and maximal field sizes. This study systematically examines the dosimetric beam properties of VHEE beams, determining their clinical usefulness while marking their limits of applications for different beam configurations. Methods: We performed Monte Carlo simulations of the dose distributions of electron beams for different energies (25–250 MeV), source‐to‐surface distances (SSD) (50 cm, 100 cm, parallel), and field sizes (2 cm 2  × 2 cm 2 to 15 cm 2  × 15 cm 2 ) in water using a research version of the RayStation treatment planning system (RaySearch Labs 9A IONPG). The beam was simulated using a monoenergetic point source and perfect collimation. Central axis percentage depth dose (PDD) and transverse dose profiles at multiple depths were evaluated and compared to those of MV photon beams. Profile characteristics including therapeutic range (TR) at 90%, proximal fall‐off (PFO) at 90%, lateral penumbra (LP) at 90%–10%, and field width (FW) at 90% were obtained. Results: Very high‐energy electrons beams with SSD 100 cm and parallel beams (infinite SSD) exhibit a linear to near‐linear increase of TR as a function of energy in the simulated energy range and reach values well beyond the typical depths of lesions encountered in clinics (<20 cm). Their TR show a marked field size dependence only for field sizes <10 cm 2  × 10 cm 2 . For VHEE beams with SSD 50 cm, TR are largely reduced (4–8 cm). For beam energies >150 MeV with large SSD (>100 cm), for many configurations, there is no substantial difference in PDD when adding an opposed beam. This may potentially reduce the number of VHEE beams needed for treatment by a factor of two compared to a treatment using lower energies and lower SSD. In order to cover deep‐seated targets homogeneously, VHEE devices with a parallel beam must provide a maximum field size up to several centimeters larger than the tumor size. For the investigated diverging beams, there is not such a significant field width reduction with depth for larger fields as it is compensated by divergence. Penumbrae of VHEE beams are smaller than those of clinical MV photon beams for lower depths (<5 cm) but increase quickly for larger depths. There is only a relatively small dependence of penumbra on the SSD of the beam. Conclusions: The findings presented in this study assess the performance of VHEE beams and offer a first estimate of treatment indications and tradeoffs for a given design of a VHEE device. SSD >100 cm results in clinically more favorable PDD. Beam energies of 100 MeV and above are needed to cover common tumors (5–15 cm in‐depth) conformally. Higher energies provide an additional benefit specifically for small and deep‐seated lesions due to their reduced lateral penumbrae.